Targeted demersal fish species exhibit variable responses to long-term protection from fishing at the Houtman Abrolhos Islands - Bornt, K.; McLean, D.; Langlois, T.; Harvey, Euan; Bellchambers, L.; Evans, S.; Newman, Stephen (Springer Verlag, 2015)
Natural fluctuations in the abundance and length of targeted fish are often disrupted by acute environmental changes and anthropogenic impacts, particularly fishing pressure. Long-term assessments of targeted fish populations inside and outside areas closed to fishing are often necessary to elucidate these effects, yet few of these studies extend over long time periods. We assessed trends in the abundance and length of six targeted fish species in areas open and closed to fishing on seven occasions spanning a 9-year period (2005–2010 and 2013) at the Houtman Abrolhos Islands, Western Australia. Shallow (8–12 m) and deep (22–26 m) coral-dominated reef sites were sampled across four geographically separated island groups using baited remote underwater stereo-video (stereo-BRUV). Between 2005 and 2010, populations of Lethrinus miniatus, Lethrinus nebulosus, Plectropomus leopardus, and Chrysophrys auratus became increasingly dominated by larger individuals, potentially indicative of an ageing population. Between 2010 and 2013, however, there was a significant increase in the proportion of smaller L. miniatus, L. nebulosus, and P. leopardus in both open and closed areas, reflecting increased recruitment perhaps due to changing environmental conditions associated with a marine heat wave anomaly.This recruitment pulse was not observed for the other species in this study (Chr. auratus, Choerodon rubescens, and Glaucosoma hebraicum). Lethrinus miniatus, L. nebulosus, Chr. auratus, and P. leopardus were larger in closed areas relative to open areas; however, they were not more abundant. These complex responses to protection also varied across sampling years for certain species (e.g., P. leopardus). Monitoring changes over the long-term in areas open and closed to fishing provides a sound basis for separating environmental variability from that associated with fishing mortality, which is crucial for optimising fisheries management.